The Effect of Solid Content Percentage and Concentration of Dispersing Agent (Anionic-Nonionic) on Quality of Polyester Dyed Fabric with Disperse by High Temperature/Pressure Method - Maulana Fahrizal Abdan; Maya Komalasari; Rendy Ardyansyah (Sainteks: Jurnal Sain dan Teknik, 2022)
This study aims to determine the % solid content to the determination of the concentration of the dispersing agent / leveler. Therefore, in order to determine the correct concentration, the % solid content varied, namely 43.930%, 21.975%, and 14.650%, with each concentration of dispersing/averaging agent 0 g/l, 0.5 g/l, 0.75 g /l, and 1.5 g/l. Furthermore, preliminary testing of solid content and dispersing power was carried out before the immersion application. The results of the most optimal dispersing power test were obtained at a variation of the concentration of the dispersing agent/average 1.5 g/l with a solid content of 43.93%. The results of the dyeing process were evaluated related to testing for color evenness, color aging, color fastness to washing, and rubbing. Based on the results of tests and evaluations, it shows that the variation of %solid content and concentration of dispersing agent/leveler has no effect on the value of color fastness to washing and rubbing. However, solid content and concentration of dispersing agent/leveler have an effect on color evenness, and color darkening. In this experiment, it can be seen that the most optimal color darkening is 28.1380, while the most optimal standard deviation of 0.187 is found in the concentration of dispersing agent/average of 1.5 g/l with a solid content value of 43.93%. The value of color fastness to wet and dry rubbing is 4-5.